Composition and paleoecology of the mid-Jurassic bony fish assemblage of the Vaches Noires cliffs (Normandy, France) - Simon Beaufils; Romain Vullo; Damien Gendry; Laurent Picot; Lionel Cavin (PLoS ONE, 2026)
The Callovian fossil assemblage of the Vaches Noires cliffs in Normandy, France has played an important role in French paleontology since the end of the 18 th century. The bony fish component, which includes coelacanths and ray-finned fishes, is represented mainly by fragmentary material. In this study, we provide the first overview of the bony fish assemblage by examining isolated remains collected mostly by amateur paleontologists over the years and housed in public collections. The assemblage comprises remains of Actinistia ( Trachymetopon sp.), Pachycormidae are represented by the filter feeder asthenocormin Leesdichthys problematicus , and by hypsocormin Hypsocormus cf. leedsi and Orthocormus cf. tenuirostris . Ginglymodi are represented by cranial elements of cf. Scheenstia and Halecomorphi by ‘Eurypoma ’ grande . Pycnodontiformes ( Mesturus sp. and Athrodon sp.) are represented by isolated vomers and prearticulars. The presence of small-sized actinopterygians is attested by small amphicoelous vertebrae. For each taxon, estimated body size and trophic level are inferred through comparisons with extant ecological analogs. Finally, we compare the Vaches Noires assemblage with other Jurassic fish assemblages to assess broader evolutionary and ecological trends in bony fish diversity during the Jurassic.